A peptide-based supercapacitor and its performance improvement via TiO2 coating. Issue 17 (19th April 2018) - Hu, Kuan; Zheng, Chao; An, Miao; Ma, Xiaohui; Wang, Lu
Abstract : Based on their ability to self-assemble and mimic strategies that occur in nature, peptide nanomaterials offer a variety of potential applications in environmentally friendly energy storage technologies. Abstract : Based on their ability to self-assemble and mimic strategies that occur in nature, peptide nanomaterials offer a variety of potential applications in environmentally friendly energy storage technologies. Herein, we report the experimental investigations into an elaborate self-assembled dipeptide Fmoc-EF-NH2, which displayed good performance as an electrode material in a supercapacitor. In order to protect the peptide electrode from electrolyte dissolution, a thin layer of TiO2 was coated on the peptide film by atomic layer deposition. The as-prepared peptide electrodes achieved an outstanding mass-specific capacitance of 125 F g −1 at 0.1 A g −1 current density and an areal capacitance of 8.6 mF cm −2 . Furthermore, the capacitor exhibits excellent stability, in that 95% of the capacitance was retained after 5000 cycles. Additionally, the fabricated all-solid-state SCs possess excellent mechanical flexibility. To the best of our knowledge, this is the first investigation that comprehensively assessed the electrochemical performance of peptide materials.